EFFECT OF BIOINOCULATION OF BACTERIA ,FUNGIA ,THE ADDITION OF PHOSPHATE ROCK IN AVAILABILITY NPK ONCORN RHIZOSPHERE - Arabi, Hatem; Hasan, Kareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate effect of a field experiment was carried out at the Agricultural Research and Experiments Station College of Agricultural Engineering Sciences - University of Baghdad in the spring season of 2023 with the aim of studying the effect of two factors. The first factor is the bioinoculation at three levels (without inoculation , Pseudomonas fluorescens, and Glomas mossae). The second factor is three levels of phosphate rock (without addition, 50 and 100%) of half the fertilizer recommended equivalent used in the study. The treatment were distributed in a factorial experiment according to a completely randomized block design. the single inoculation of bacteria and fungi and the addition of phosphate rock have affected all the studied properties, while the double interaction of the biological and fungal inoculum treatments and the 50% level of phosphate rock equivalent to half the recommended fertilizer showed the highest averages for NPK properties in the corn rhizosphere, which reached (64.23, 20.24, 246.92 mg. kg-1 soil), respectively in comparison to the control treatment that gave the lowest averages in all the above traits which reached (48.71, 9.65, 176.07 mg kg-1 soil).